KAJIAN HISTORIS TERHADAP GERAKAN HIZBUTTAHRIR DI KALIMANTAN SELATAN - ., Maimanah; Hakim, Abdul; Yulizar, Muhammad Adriani (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2009)
This writing is based on the research on Hizbuttahrir of South Kalimantan in historical perspective. From the research found that the coming of Hizbuttahrir in South Kalimantan started in 1990 by the two activist, Reza Rosadi and Ismanto. For the first time, Hizbuttahrir introduced through the discussion club or halaqah around campus. Later, it became the religion movement. The issues that developed by Hizbuttahrir of South Kalimantan is the enlightement of the society religion that they are able to practice the Islam totally in any life perspective.